The complex response of free and bound amino acids to water stress during the seed setting stage in Arabidopsis. (5th February 2020) - Yobi, Abou; Bagaza, Clement; Batushansky, Albert; Shrestha, Vivek; Emery, Marianne L.; Holden, Samuel; Turner‐Hissong, Sarah; Miller, Nathan D.; Mawhinney, Thomas P.; Angelovici, Ruthie
Summary: Free amino acids (FAAs) and protein‐bound amino acids (PBAAs) in seeds play an important role in seed desiccation, longevity, and germination. However, the effect that water stress has on these two functional pools, especially when imposed during the crucial seed setting stage is unclear. To better understand these effects, we exposed Arabidopsis plants at the seed setting stage to a range of water limitation and water deprivation conditions and then evaluated physiological, metabolic, and proteomic parameters, with special focus on FAAs and PBAAs. We found that in response to severe water limitation, seed yield decreased, while seed weight, FAA, and PBAA content per seed increased. Nevertheless, the composition of FAAs and PBAAs remained unaltered. In response to severe water deprivation, however, both seed yield and weight were reduced. In addition, major alterations were observed in both FAA and proteome compositions, which indicated that both osmotic adjustment and proteomic reprogramming occurred in these naturally desiccation‐tolerant organs. However, despite the major proteomic alteration, the PBAA composition did not change, suggesting that the proteomic reprogramming was followed by a proteomic rebalancing. Proteomic rebalancing has not been observed previously in response to stress, but its occurrence under stress strongly suggests its natural function. Together, our data show that the dry seed PBAA composition plays a key role in seed fitness and therefore is rigorously maintained even under severe water stress, while the FAA composition is more plastic and adaptable to changing environments, and that both functional pools are distinctly regulated. Significance Statement: Imposing severe water deprivation or limitation on Arabidopsis plants during the seed setting stage has differing effects on the free amino acid composition of dry seeds. The composition of protein‐bound amino acids, in contrast, is rigorously maintained via distinct molecular mechanisms depending on the water stress imposed; one mechanism being proteomic rebalancing, which only occurs in response to severe water deprivation. The latter phenomenon has not been previously reported as a response to stress.